The Effectiveness of Edmodo as a Professional Learning Network (PLN) on Students' Achievement and their Motivations toward it - Al-Said, Khaleel M. (Opción, 1970)
The purpose of this study was to examine the effectiveness of Edmodo as a Professional Learning Network (PLN) on students' achievement and their motivations toward it in the e-learning course and also to determine the level of their motivations toward Edmodo. The findings of the study affirmed the effectiveness of Edmodo as (PLN) on students' achievement at the cognitive domain, and also it has been indicated a clear effectiveness of Edmodo on motivations for the majority of students toward it, as well as the students' motivations level toward Edmodo was in high level since they considered it as an effective participatory tool for discussions and exchange ideas and knowledge